Literature Review Analisis Hambatan Pada Aksesbilitas Pendidikan Bagi Anak Jalanan - Rendy Aulia Birkil; Hastin Trustisari (Kampus Akademik Publiser, 2024)
Every child, including neglected children, has the right to education, from all forms of obstacles to access to education for street children. This study aims to analyze barriers to access to education for street children. This assessment method uses a descriptive literature review conducted online regarding barriers to street children's access to education. The results of the online literature review contained 1 article including Google Scholar. The results of the study illustrate (1). seven articles about the educational rights of street children (2). Challenges and obstacles in street children's education (3) two articles about street children's education programs. Based on this, equal education for street children is an important and relevant effort to provide them with equal opportunities in education and overcome their socio-economic problems. The recommendation from this study is to develop more flexible learning methods according to the needs and situations of street children, including the use of technology or more interesting learning media. KEYWORDS: Accessibility, Education, Street Children.